The methodological dance: critical reflections on conducting a cross-cultural comparative research project on 'Sport for Development and Peace'. Issue 5 (19th October 2016) - Collison, Holly; Giulianotti, Richard; Howe, P. D.; Darnell, Simon
Abstract: Social scientific research requires engagement with individuals, groups and or organisations embedded within specific sectors and locations. The 'Sport for a Better World?' project aimed to examine the Sport for Development and Peace (SDP) sector within multiple international locations through fieldwork conducted by a four-person research team. This paper discusses the methodological benefits and challenges of this methodological approach, with a particular focus on working with individuals and groups as gatekeepers, encultured informants, translators and volunteers. In turn, we describe and contextualise the levels of exchange expected by stakeholder partners as well as the implications of our identity as white, international researchers. Overall, we argue for the importance of understanding: the agency and needs of local actors amidst transnational networks; the extent to which history and politics inform everyday experiences and contemporary research encounters; and the likelihood that unequal power relations, particularly along lines of race, class and geography will affect data collection and interpretation. We also discuss various methodological strategies we negotiated in-the-field, and how these insights inform our understandings of the social, political and cultural environment in which SDP programmes operate in different locations.